2022
DOI: 10.1016/j.celrep.2021.110189
|View full text |Cite
|
Sign up to set email alerts
|

CXCL4 drives fibrosis by promoting several key cellular and molecular processes

Abstract: Highlights d CXCL4 is increased in multiple fibrotic models resembling systemic sclerosis d Absence of CXCL4 diminishes and overexpression aggravates bleomycin-induced fibrosis d CXCL4 promotes myofibroblast transformation and collagen production d CXCL4-induced endothelial-to-mesenchymal transition involves metabolic changes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 96 publications
4
26
0
Order By: Relevance
“…CXCL4 has been validated to stimulate endothelial-to-mesenchymal transition in fibrotic tissues. Myofibroblast differentiation and collagen synthesis are directly induced, indicating that CXCL4 may be a potential therapeutic target for the treatment of fibrosis and scars [ 55 ]. Meanwhile, N-cadherin has been shown to be critical in injury-triggered swarming, as well as migration of fascia fibroblasts that progressively contract the skin and form scars [ 56 ].…”
Section: Regulation Of Fibroblasts In Wound Healing and Scar Formationmentioning
confidence: 99%
“…CXCL4 has been validated to stimulate endothelial-to-mesenchymal transition in fibrotic tissues. Myofibroblast differentiation and collagen synthesis are directly induced, indicating that CXCL4 may be a potential therapeutic target for the treatment of fibrosis and scars [ 55 ]. Meanwhile, N-cadherin has been shown to be critical in injury-triggered swarming, as well as migration of fascia fibroblasts that progressively contract the skin and form scars [ 56 ].…”
Section: Regulation Of Fibroblasts In Wound Healing and Scar Formationmentioning
confidence: 99%
“…Using the bleomycin (BLM)-induced skin fibrosis model, we have reported that pDCs are key players in the establishment and maintenance of skin fibrosis ( Ah Kioon et al, 2018 ). In addition, we observed that CXCL4 is induced in the skin of the BLM-treated mice ( Ah Kioon et al, 2018 ), and it was recently shown that CXCL4-deficient mice do not progress to fibrosis in BLM-treated mice ( Affandi et al, 2022 ). Hence, in this model, the CXCL4 is endogenously produced and associated with disease.…”
Section: Resultsmentioning
confidence: 93%
“…CD14, which is engaged in toll-like receptor signaling by LPS, is expressed by these cells at high levels (Figure 2C, Figure S3B). Cluster 4 expresses transcripts involved in fibrosis, including Pf4, CD206, and Stab1 (Fig S3C) (14)(15)(16)(17)(18). Cluster 5 can be distinguished by the expression of Vim, Ccl2, Tnip3, and Ccr2 transcripts (Figure 2C, Figure S3D).…”
Section: Delineation Of Transcriptionally Distinct Kidney Resident Ma...mentioning
confidence: 99%